2007
DOI: 10.1063/1.2773716
|View full text |Cite
|
Sign up to set email alerts
|

Understanding fragility in supercooled Lennard-Jones mixtures. I. Locally preferred structures

Abstract: We reveal the existence of systematic variations of isobaric fragility in different supercooled Lennard-Jones binary mixtures by performing molecular dynamics simulations. The connection between fragility and local structures in the bulk is analyzed by means of a Voronoi construction. We find that clusters of particles belonging to locally preferred structures form slow, long-lived domains, whose spatial extension increases by decreasing temperature. As a general rule, a more rapid growth, upon supercooling, o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
279
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(310 citation statements)
references
References 58 publications
(105 reference statements)
28
279
2
1
Order By: Relevance
“…A number of simulation studies [15,17,18,28] have suggested that in one possible scenario crystallization might be hindered by the emergence in the bulk supercooled liquid of locally preferred structures that eventually are incompatible with long-range crystalline order [34]. One important example is the icosahedron with its fivefold symmetry [35], which has been recently found to be a fundamental geometrical motif in the structure of bulk metallic glasses [36].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A number of simulation studies [15,17,18,28] have suggested that in one possible scenario crystallization might be hindered by the emergence in the bulk supercooled liquid of locally preferred structures that eventually are incompatible with long-range crystalline order [34]. One important example is the icosahedron with its fivefold symmetry [35], which has been recently found to be a fundamental geometrical motif in the structure of bulk metallic glasses [36].…”
mentioning
confidence: 99%
“…As the next step we looked at the bulk structural features, which offer important insights into the behavior of supercooled liquids [4,15,17,28]. To access static structural properties of the nonequilibrium pH 2 -oD 2 quantum liquid mixtures we have carried out path-integral Monte Carlo (PIMC) simulations [29] by using a canonical [30] Worm algorithm [31].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(17), when i = 8, q 8,R ≈ 2.137σ 1 > 2σ 1 , (q 7,R < 2σ 1 ), and q 8,R -q 1 ≈ 2.032 σ 1 > 2σ 1 . Therefore, only in the 8th order of L-J potential field, the spacing between the 8th order and the first order of sharp-angled point is more than 2σ 1 and is able to place a σ 1 hard-cluster in between.…”
Section: B Proof For 8 Orders Of Molecule-clustersmentioning
confidence: 99%
“…Lennard -Jones (L-J) potential is widely used to describe molecule-cluster interactions and glass transition (GT), [1][2][3][4][5][6] However, the fundamental theory to unify the mechanisms for the truncated L-J potential, 7-9 the presence of long-ranged interparticle potentials, 10 the density or cluster size fluctuation stability, 11 and the two kinds of relaxations: fast and slow in current Mode-Coupling Theory, 12 the distribution of particle sizes, 13 or the core difficulty of particle size fractionation 14 in simulation are still not simply and fully established. The relationship between GT and general displacement transitions in condensed matter physics has remained obscure.…”
Section: Introductionmentioning
confidence: 99%